Palladium-Catalyzed Germylation of Aryl Bromides and Aryl Triflates Using Hexamethyldigermane - Komami, Narumi; Matsuoka, Keitaro; Yoshino, Tatsuhiko; Matsunaga, Shigeki (Synthesis, 2018)
Palladium-catalyzed germylation of aryl bromides and aryl triflates using commercially available hexamethyldigermane is described. Optimized reaction conditions afforded various functionalized aryltrimethylgermanes, including drug-like molecules, in moderate to good yields, demonstrating the versatility of the presented protocols.
Keywords: palladium catalysis; germylation; digermane; aryl bromide; aryl triflate